(untitled) (Bangladesh Journal of Urology, 2020)
Background: Posterior urethral valves are the most common cause of congenital obstructive lesion in the newborns and infant male child, occurring at the distal portion of the prostatic urethra. Diathermy fulguration of valve is one of the commonest modalities which has been practiced by Pediatric Urologist since decades where success rate ranging from 50-70%. Despite high success rate, post-operative complications like hematuria, urinary tract infections, urinary incontinence, retention of urine, residual valve and urethral stricture may develop in significant number of patients. Incision of the posterior urethral valve by cold knife is one of the modalities in the recent years with insignificant complications and good outcome with success rate ranging from 70-90%. Objective: To compare the efficacy of the cold knife with the diathermy fulguration in the management of the posterior urethral valve. Materials and Methods: This study was conducted in Urology Department of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from 1st January 2017 till 1st September 2018. A total 48 patients, diagnosed as a case of PUV and who fulfill the selection criteria were divided randomly by simple lottery method into 2 groups consisting of 24 patients in each group. Valve ablation was performed under standard aseptic condition according to groups. Patients were followed up at 3 and 6 months of initial intervention. They were re-evaluated during the follow up with history, clinical examination and investigation findings. Their subjective outcome and objective findings were assessed and compared in between the two groups. Results: There was no significant difference in the age distribution in between the groups (p= 0.083). Within the group, all the variable parameters were significantly improved prior and after the intervention. But, in between the groups, after 6 months of intervention, there was no difference in improvement of urinary flow(p=0.695). Incontinence of urine was not significant (p=1.000). The drop of mean serum creatinine level was not significant (p=0.530). Decrease in Mean PVR was not significant (p=0.684). Maximum flow rate was not significantly improved (p= 0.255). Peri catheter bleeding and residual valve were not significant. Stricture urethra was not found in any patient in both groups. Conclusion: Comparing the findings of the present study, it can be concluded that cold knife incision is equally effective in comparison to diathermy fulguration in the management of posterior urethral valve. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.118-127